FAKTOR-FAKTOR PENENTU KUALITAS INFORMASI AKUNTANSI PADA INSTANSI PEMERINTAH - Munthe, Fachrurozy Mikraj; Suazhari, Suazhari (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2024)
This research examines the influence of accounting understanding, information technology utilization, and information system user capability on the quality of accounting information. This research includes quantitative research. The population in this research is all regional apparatus in the Medan City Government, which consists of 27 regional apparatus. The sample was determined using census research. The total sample in this study was 108 respondents, composed of staff of financial administration officials, treasurers, program preparers, and heads of agencies at the Medan City Government. The sample obtained after distributing the questionnaire was 68 respondents. This research uses primary data by distributing questionnaires via Google Forms. The influence test of independent variables toward dependent variables employs a multiple linear regression model. The research results show that accounting understanding, information technology utilization, and information system user capability influence the quality of accounting information. The results also show that understanding accounting, information technology utilization, and information system user capability influence the quality of accounting information partially.